How skeptics do ethics : a brief history of the late modern linguistic turn - Neal, Aubrey, 1946- (University of Calgary Press, 2007)
Enlightenment philosophers are often credited with formulating many theories about humankind and society, and in our post-modern age, we still live with some of the very same compelling, contentious and often unresolved questions about ourselves and the world we live in. Author Aubrey Neal suggests that one of these issues that lingers with us today is scepticism, and in "How Skeptics do Ethics", he unravels the thread of this philosophy from its origins in enlightenment thinking down to our present age. He contends that linguistics and language have not brought modern philosophy any closer to understanding the role and nature of ethics in our current science-based society. Going further, Neal suggests the contemporary reader meets traditional terms for ethical theory, plausible belief and moral action in a different world from the one in which they were coined. Instead, these considerations for modern thinkers require a coherent language practice suitable for the social context in which we live, and thus raise the question of the meaning of old philosophical debates and their value for our society today.; Referencing such luminary thinkers as Hume, Kant, and Hegel, Neal seeks to re-ignite age old questions and awaken the reader to a sense that our contemporary modes of reference and understanding should be seen from a substantially different point of view. Challenging, bracing, and entirely unflinching, "How Skeptics do Ethics" is a wake-up call for anyone who thinks seriously about our society, ourselves, and the world in which we live